Chronic and Residual Effects of a Two-Week Foam Rolling Intervention on Ankle Flexibility and Dynamic Balance - Seever, Thomas Christoph; Mason, Joel; Zech, Astrid (Frontiers in Sports and Active Living, 2022)
Background: Foam rolling has been shown to acutely improve joint range of motion (ROM). However, limited knowledge exists on the chronic and residual effects. The primary purpose of this study was to examine the chronic and residual effects of a two-week roller-massager intervention on ankle dorsiflexion ROM and dynamic balance. Methods: Forty-two participants (24.3 ± 2.5 years, 33 males, 9 females) were randomly assigned to either roller-massage (RM) or control group (= no intervention). Ankle ROM was assessed with the weight-bearing lunge test (WBLT) and dynamic balance with the Y-Balance test for both limbs. The RM group was instructed to roll their calf muscles for 3 sets of 60 sec per leg on six days a week over two weeks. Acute effects were measured during baseline testing for dorsiflexion ROM and dynamic balance immediately after foam rolling. Chronic and residual effects were measured one day and seven days after the intervention period. Multivariate ANOVA was performed for post hoc comparisons to determine acute, chronic, and residual effects. Results: Significant acute and chronic foam rolling effects (p < 0.05) were found for ankle dorsiflexion ROM. The chronic increase in ROM slightly decreased seven days post-intervention but remained significantly above baseline (p < 0.05). Regarding dynamic balance, there were no acute but chronic (p < 0.05) and residual (p < 0.05) effects. Conclusion: Using a roller-massager for a two-week period chronically increases ROM and dynamic balance. These increases are still significant seven days post-intervention emphasizing the sustainability of foam rolling effects.